Elastic-band resistance exercise or vibration treatment in combination with hydroxymethylbutyrate (HMB) supplement for management of sarcopenia in older people: a study protocol for a single-blinded randomised controlled trial in Hong Kong - Chow, Simon Kwoon-Ho (BMJ Open, 2020)
INTRODUCTION: Sarcopenia is a geriatric syndrome characterised by progressive loss of skeletal muscle mass and function with risks of adverse outcomes and becomes more prevalent due to ageing population. Elastic-band exercise, vibration treatment and hydroxymethylbutyrate (HMB) supplementation were previously proven to have positive effects on the control of sarcopenia. The purpose of this study is to evaluate the effectiveness of elastic-band exercise or vibration treatment with HMB supplementation in managing sarcopenia. Our findings will provide a safe and efficient strategy to mitigate the progression of sarcopenia in older people and contribute to higher quality of life as well as improved long-term health outcomes of elderly people. METHODS AND ANALYSIS: In this single-blinded, randomised controlled trial (RCT), subjects will be screened for sarcopenia based on the Asian Working Group for Sarcopenia (AWGS) definition and 144 sarcopenic subjects aged 65 or above will be recruited. This RCT will have three groups evaluated at two time points to measure changes over 3 months—the control and the groups with combined HMB supplement and elastic-band resistance exercise or vibration treatment. Changes in muscle strength in lower extremity will be the primary outcome. Muscle strength in the upper extremity, gait speed, muscle mass (based on AWGS definition), functional performance in terms of balancing ability and time-up-and-go test and quality of life will be taken as secondary outcomes. In addition, each participant’s daily activity will be monitored by a wrist-worn activity tracker. Repeated-measures analysis of variance will be performed to compare within-subject changes between control and treatment groups at two time points of pretreatments and post-treatments. ETHICS AND DISSEMINATION: The procedures have been approved by the Joint CUHK-NTEC Clinical Research Management Office (Ref. CREC 2018.602) and conformed to the Declaration of Helsinki. Results will be disseminated through peer-reviewed publications, conferences and workshops. TRIAL REGISTRATION NUMBER: NCT04028206.